MICROVESSELS, MAJOR DISCOVERIES: EXPLORING VASCULAR DISEASES ON CHIPS (CIPEEX, 2025)
Introduction: Cardiovascular diseases remain leading causes of morbidity and mortality worldwide, and understanding their mechanisms is still restricted by animal models and traditional cell cultures, which fail to reproduce the human microenvironment. In this context, organ-on-chip devices and microfluidic platforms have emerged as innovative systems capable of integrating molecular, cellular, and hemodynamic variables into biomimetic models. These devices require small amounts of blood, are cost-effective, reproducible, and allow the creation of microvasculatures resembling human anatomy, including bifurcations and plaques, enabling real-time analysis with imaging. Customization with genetically modified cells, along with control of variables such as platelets, coagulation proteins, and leukocytes, reinforces their relevance for translational medicine. Objective: This study aims to demonstrate the potential of microfluidic platforms to model the pathophysiology of human vascular diseases, reproducing microvasculature, hemodynamic forces, and cellular interactions, with the goal of improving understanding of vascular dysfunction and supporting new therapeutic strategies. Methodology: This is a narrative literature review using PubMed and Scielo, analyzing articles published in the last five years. The selection emphasized studies on microvessel construction techniques and their application as innovative approaches to clarify the dynamics of vascular diseases and enable the development of effective, non-invasive treatments. Results: Emerging technologies, such as three-dimensional vessel-on-chip models derived from induced pluripotent stem cells (hiPSCs), reproduce vascular anatomy in stable networks with perfusion and allow investigation of disease mechanisms. Specific models, including “atherosclerosis-on-a-chip” and “thrombosis-on-a-chip,” support studies on endothelial dysfunction, plaque instability, thrombus dynamics, stenosis geometries, and thrombogenic factors. Controlling parameters such as shear stress, matrix stiffness, and inflammatory cytokines simulates different disease stages. Integrating microfluidic platforms thus represents a tool for exploring vascular pathogenesis through signaling pathways, remodeling, and regression, while supporting drug testing. Polydimethylsiloxane (PDMS) is widely used due to transparency, biocompatibility, and oxygen permeability. Constructing the extracellular matrix (ECM) is crucial, achievable with natural hydrogels, which mimic human ECM, or synthetic ones, which allow more control. Fabrication usually involves soft lithography to mold PDMS, while three-dimensional bioprinting enables deposition of bioinks into complex scaffolds. Combining natural and synthetic polymers ensures stability and biochemical fidelity. To reproduce vascular homeostasis—including stretching and shear stress—devices with two channels separated by a PDMS membrane deform under vacuum, mimicking smooth muscle stretching. Other systems apply continuous flow over elastic membranes with peristaltic pumps to combine shear and deformation in endothelial cells. Incorporation of nanomaterials such as carbon nanotubes, graphene oxide, and gold nanorods improves printability, conductivity, and stability, generating accurate constructs. Advanced bioprinting strategies, including in situ curing, support bath methods, and ion- or temperature-mediated crosslinking, further enhance fidelity. Conclusion: Microfluidic platforms have advanced the study of vascular dysfunction by reproducing features such as rigidity, endothelial permeability, and microvascular obstruction, all present in progressive circulatory disorders.The ability of these devices to reproduce complex hemodynamic and anatomical conditions in real time enhances understanding of cellular and molecular mechanisms in vascular disease, consolidating their role as promising tools for innovative and targeted therapeutic strategies.
Keywords: Microphysiological Systems; Vascular Diseases; Microfluidics